Chloral hydrate sedation for magnetic resonance imaging in newborn infants. Issue 2 (24th September 2013) - Finnemore, Anna; Toulmin, Hilary; Merchant, Naz; Arichi, Tom; Tusor, Nora; Cox, David; Ederies, Ash; Nongena, Phumza; Ko, Christopher; Dias, Ryan; Edwards, Anthony D.; Groves, Alan M.; et al.
Summary Background The aim of this study was to look for clinically significant adverse effects of chloral hydrate used in a large cohort of infants sedated for magnetic resonance imaging. Method Case notes of infants who underwent magnetic resonance imaging (MRI) scanning from 2008 to 2010 were reviewed, with patient demographics, sedation dose, comorbidities, time to discharge, and side effects of sedation noted. Results Four hundred and eleven infants (median [range] postmenstrual age per weight at scan 42 [31+4–60] weeks per 3500 g [1060–9900 g]) were sedated with chloral hydrate (median [range] dose 50 [20–80] mg·kg−1). In three cases (0.7%), desaturations occurred which prompted termination of the scan. One infant (0.2%) was admitted for additional observation following sedation but had no prolonged effects. In 17 (3.1%) cases, infants had desaturations which were self‐limiting or responded to additional inspired oxygen such that scanning was allowed to continue. Conclusion When adhering to strict protocols, MRI scanning in newborn infants in this cohort was performed using chloral hydrate sedation with a relatively low risk of significant adverse effects.